0697 The Relationship Between Anger Expression and Sleep - David, Michelle; Sedano, Brandon Fernandez; Shurovi, Sumayya; Yurgel, Tyla; Cornelius, Talea; Schwartz, Joseph; Abdalla, Marwah (Sleep (New York, N.Y.), 2023)
Introduction Increased anger expression (AE) is linked to worse health outcomes. Short sleep duration and poor sleep quality are linked with increased anger. However, few data have examined whether increased AE may lead to disturbed sleep. We examined if AE is associated with objectively and subjectively-assessed sleep measures in two cohort studies. Methods The Masked Hypertension Study (MHTN, n=888) is a multi-site study of the prevalence and predictors of masked hypertension. Participants completed the Spielberger Anger Expression Scale (SAES) and the Pittsburgh Sleep Quality Index. Sleep duration and percent of time awake after sleep onset (%waso) during a 24-h period were derived from wrist-worn actigraphy (ActiWatch; Phillips Respironics), supplemented by diary reports. The Worksite Blood Pressure study (WSBPS, n=472) is a multi-site study of psychological factors and ambulatory blood pressure. Participants completed the SAES and a sleep quality questionnaire. In MHTN, linear regression models were estimated for each sleep outcome with age, sex, race/ethnicity, and anxiety as covariates. In the WSBPS, the analysis was conducted for sleep quality only, controlling for age, race/ethnicity, anxiety, sleep apnea, and study site. Results Participants in MHTN (n=782) were 59.5% female, 11.5% Hispanic/Latinx. Mean age was 45.5 years (SD = 10.4). Mean AE was 34.7 (SD = 6.6). Mean sleep duration was 6.3 hours (SD = 1.1), mean %waso was 7.1% (SD = 4.0), and mean sleep quality was 5.6 (SD = 3.2). AE was not significantly associated with sleep duration, B = 0.01, 95% CI -0.01, 0.02, p = .30, waso, B = 0.02, 95% CI -0.03, 0.07, p = .43, or sleep quality, B = 0.01, 95% CI -0.03, 0.05, p = .71. Participants in WSBPS (n=278) were 23.7% female, 6.1% Hispanic/Latinx and mean age was 53.1 years (SD = 8.5). Mean AE was 46.8 (SD = 5.0). Mean sleep quality was 8.4 (SD = 4.4). AE was not significantly associated with sleep quality, B = -0.014, 95% CI 0.14, 0.07, p = 0.50. Conclusion AE was not associated with objective or subjectively-assessed sleep measures. Our findings may suggest that clinicians should focus on other factors rather than AE to improve sleep. Support (if any) P01HL47540